On isothermality in some commonly used plug flow reactors for X-ray based investigations of catalysts. Issue 12 (31st May 2019) - Newton, Mark A.; Checchia, Stefano; Knorpp, Amy J.; Stoian, Dragos; van Beek, Wouter; Emerich, Hermann; Longo, Alessandro; van Bokhoven, Jeroen A.
Abstract : We compare two reactor setups commonly used to make operando measurements of catalyst behavior using X-rays in terms of the degree to which they may be considered to yield radial and axial isothermality. Abstract : We compare two reactor setups commonly used to make operando measurements of catalyst behavior using X-rays in terms of the degree to which they may be considered to yield radial and axial isothermality. We use axial and radial Cu K-edge XANES mapping of copper containing zeolites after high temperature activation (773 K) in oxygen and subsequent exposure to methane (473 K), to demonstrate the ease with which it is possible to enter into substantially non isothermal situations using air blower systems of a type commonly utilized. The implications of these observations for the attainment of non-representative structure–function relations are discussed. We further show, using this chemistry and infrared imaging, how this unwanted situation can be ameliorated by adopting a different type of reactor and point out that, even in this case isothermality should not be taken for granted and should be actively verified prior to experimental investigation.